English Education at Elementary School in Japan - Novita Triana (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2017)
This paper aims to discuss the implementation of English education in elementary school in Japan. What challenges faced by the implementation of English education in elementary school. This paper reviewed some articles and book chapter regarding teaching English at elementary school in Indonesia and Japan, and the principles of teaching English to young learners (TYL). First, it provides an overview of the characteristics of young learners and challenges faced by teachers in the teaching English to young learners. Second, it will briefly describe the history of English education in Japan, followed by the discussion of the present implementation of English education at elementary schools. Finally, it relates the discussion of English education at elementary school to Indonesian context.Key Words; English Education, Elementary School, TYL